Evaluation of microRNA expression profiling in highly metastatic laryngocarcinoma cells. (2nd December 2018) - Chen, Liwei; Liu, Shaoyan; Li, Kun; Qi, Jixia; Liu, Chenqing; Zong, Liang; Zhang, Yongxia; Zhao, Jiandong; Zhai, Xingyou; Li, Jianhui; Kong, Xinru; Yang, Shiming; et al.
Abstract: Background: Until now, little is known about the role of miRNAs in the invasion and metastasis of Laryngeal squamous cell carcinoma (LSCC). Objectives: This study aimed to explore the relationship between microRNA and the invasion and metastasis of LSCC. Material and methods: The highly metastatic laryngocarcinoma cells were obtained from the established animal model with spontaneous lymph node metastasis of LSCC in our previous study. MicroRNA expression profiling and bioinformatic analysis were performed to analyze the microRNA expression changes in the highly metastatic laryngocarcinoma cells and the parental tumor cells (HEP-2). RT-PCR was performed for further validation of the result of microarray. Results: A total of 40 microRNAs were found to be significantly altered in the highly metastatic laryngocarcinoma cells compared to controls. Bioinformatic analysis identified that 19 key microRNAs might involve in LSCC development. Moreover, RT-PCR confirmed that miR-25, miR-100, miR-125b-5p and let-7g were differentially expressed in different laryngocarcinoma cells and human tumor specimens. Conclusions and significance: Our findings suggest that microRNA play an important role in the invasion and metastasis of LSCC, and provide the clues for studying the function of microRNA as well as opportunities to analyze the complex molecular abnormalities driving LSCC progression.